LMO2 promotes tumor cell invasion and metastasis in basal-type breast cancer by altering actin cytoskeleton remodeling - Liu, Ye (Oncotarget, 2016)
LMO2 is traditionally recognized as a pivotal transcriptional regulator during embryonic hematopoiesis and angionenesis, and its ectopic expression in T lymphocyte progenitors is closely correlated to the onset of acute T lymphocytic leukemia. However, recently studies revealed complicated expression features and dual functions of LMO2 on tumor behaviors in a variety of cancer types, including breast cancers. Basal-type breast cancer is one of the breast cancer subtypes and a prognostically unfavorable subtype among all breast cancers. Herein we found that in basal-type breast cancer specifically, high LMO2 expression was positively correlated with lymph node metastases in patients, promoted tumor cell migration and invasion and increased distant metastasis in SCID mice. Moreover, the novel function of LMO2 was achieved by its predominantly cytoplasmic location and interaction with cofilin1, which is a critical regulator in actin cytoskeleton dynamics. These findings suggest a subtype-dependent role of LMO2 in breast cancers and the potential of LMO2 as a subtype-specific biomarker for clinical practice.